Detection of Intraseasonal Oscillations in SMAP Salinity in the Bay of Bengal. Issue 14 (24th July 2018) - Subrahmanyam, Bulusu; Trott, Corinne B.; Murty, V. S. N.
Abstract: Analysis of Soil Moisture Active Passive (SMAP) mission derived sea surface salinity (SSS) during April 2015 to December 2017 in the Bay of Bengal (BoB) shows first revelation of new insight of existence of 30‐ to 90‐day and 10‐ to 20‐day period Intraseasonal Oscillations (ISOs) in SSS—all phase‐locked during August–December. The seasonal SMAP SSS anomaly (SSSA) minimum (−0.5 to −1.0 practical salinity unit, psu) occurs in October and exhibits year‐to‐year variation, while SSSA maximum (0.5 psu) occurs in June during 2015–2017. Interestingly, these ISOs encompass the negative phase of seasonal SSSA minimum (August–December) in a year and are related to seasonal variations in river discharge and surface freshwater flux (precipitation and evaporation), that in turn are impacted by the climatic events. Wavelet analysis reveals larger amplitude (−0.2 to 0.35 psu) 30‐ to 90‐day ISO in northern BoB during August–November. The northward propagation of the SSS ISOs would modulate the postmonsoon air‐sea interactions across the BoB. Plain Language Summary: National Aeronautics and Space Administration (NASA) recently launched Soil Moisture Active Passive (SMAP) mission on 31 January 2015, and the data products are available since 1 April 2015. We are able to retrieve sea surface salinity (SSS) from SMAP at a higher horizontal and lesser temporal resolution, and larger swath of 1, 000 km with higher accuracy, compared to the earlier salinity missions, Aquarius and SMOS. In this manuscript, we showed for the first time new insight of existence of different Intraseasonal Oscillations (ISOs) in salinity at 30‐ to 90‐day and 10‐ to 20‐day periods and 3‐ to 7‐day synoptic‐scale oscillations. It is essential to understand how the BoB responds to these oscillations, which have a direct bearing on the air‐sea interaction processes and development and intensification of weather disturbances. These weather disturbances are much impacted by the northward propagation of Madden‐Julian Oscillations. The summer monsoon over the BoB experiences active‐break cycles during June–September. The active phase enhances convection and provides heavy rainfall, while the break phase characterizes with less/scanty rainfall over the BoB and also on the Indian subcontinent. While there are studies on seasonal variability in the oceanic processes based on observations and model simulations, the studies pertaining to ISOs are still sparse due to nonavailability of data. Key Points: This study highlights new insight on the existence of Intraseasonal Oscillations (ISOs) in SMAP sea surface salinity in the Bay of Bengal Large amplitude in SMAP sea surface salinity is associated with 30‐ to 90‐day ISO period in the northern Bay of Bengal Large seasonal SMAP sea surface salinity variation in northern Bay of Bengal is related to the impacts of ENSO and Indian Ocean Dipole events